Leadership practices and the ethical values in Deuteronomy - Charles B Berebon (Center for Humanities and Innovation Studies, 2022)
Task-oriented and relationship-oriented leadership styles can also be classified as autocratic or participative. Both types must be understood in terms of the decision-making process they employ. The autocratic style functions autonomously, whereas the participatory style incorporates all team members in decision-making. There are several perspectives on integrated systems in leadership, but a set of shared principles is at the heart of this interconnectedness. However, these common principles strive for people’s holistic development, so family, civic, military, and religious leadership practices coexist with seamless coordination based on integrated systems. This study's endeavor addresses ontological and epistemological problems concerning the reality, being, and function of leadership. Specifically, this work investigates a leadership philosophy with specific reference to the Book of Deuteronomy of the Judeo-Christian Bible. This work argues that what the book of Deuteronomy teaches about leadership techniques is critical and basic to all the learning that can be gleaned from old and new biblical books. This is because the Torah, or Law, serves as the foundation for all teachings in the Bible, and the Torah contains the Book of Deuteronomy. Furthermore, because Moses taught the succession of teachings in the book, the leadership concept coming from the Book of Deuteronomy can be applied to nation-building. The research uses narrative and social-scientific criticism to analyze the characters and content.